S n = 1 + 4 9 + 9 3 6 + 1 6 1 0 0 + 2 5 2 2 5 + 3 6 4 4 1 + … + n 2 ( 1 + 2 + … + n ) 2
Evaluate S 1 6 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very simple to understand. Thanks for showing the generalization as well.
For clarity, you might want to mention that 1 + 2 + 3 + … + n = 2 n ( n + 1 ) and 1 2 + 2 2 + … + n 2 = 6 n ( n + 1 ) ( 2 n + 1 ) .
One might argue that applying Nicomachus's Theorem can be shorter. Don't you think?
@Calvin Lin , I have edited it just now to make it seem more like a solution than a comment on Chew's solution below.
Regarding the sum formulas you mentioned, they are quite elementary and known to most, I'd say. Still, if anyone doesn't know about it, they can see the Sum of n, n², or n³ wiki on Brilliant.
@Prasun Biswas , we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments.
S 1 6 = 1 + 4 9 + 9 3 6 + 1 6 1 0 0 + 2 5 2 2 5 + 3 6 4 4 1 + . . . + a 1 6 = ( 1 1 ) 2 + ( 2 1 + 2 ) 2 + ( 3 1 + 2 + 3 ) 2 + . . . + ( 1 6 1 + 2 + 3 + . . . + 1 6 ) 2 = k = 1 ∑ 1 6 ( k ∑ i = 1 k i ) 2 = k = 1 ∑ 1 6 ( 2 k k ( k + 1 ) ) 2 = k = 1 ∑ 1 6 ( 2 k + 1 ) 2 = 4 1 k = 1 ∑ 1 6 ( k 2 + 2 k + 1 ) = 4 1 ( k = 1 ∑ 1 6 k 2 + 2 k = 1 ∑ 1 6 k + k = 1 ∑ 1 6 1 ) = 4 1 ( 6 1 6 ( 1 6 + 1 ) ( 3 2 + 1 ) + 2 2 ( 1 6 ) ( 1 6 + 1 ) + 1 6 ) = 4 4 6
As Prasun had already pointed out, your penultimate step is unnecessary. Nevertheless, good work.
There is no need to expand the ( k + 1 ) 2 like that. Just shift the index.
k = 1 ∑ 1 6 ( 2 k + 1 ) 2 = 4 1 k = 2 ∑ 1 7 k 2 = 4 1 ( 6 1 ( 1 7 ) ( 1 7 + 1 ) ( 3 4 + 1 ) − 1 2 ) = 4 4 6
You can also write down the general result for S n which is,
S n = 4 1 ( 6 ( n + 1 ) ( n + 2 ) ( 2 n + 3 ) − 1 ) ∀ n ∈ Z +
Problem Loading...
Note Loading...
Set Loading...
Before reading this solution, one might want to read up on Sum of n, n², or n³ wiki.
The sum equals to,
S n = k = 1 ∑ n ( k ∑ i = 1 k i ) 2 = k = 1 ∑ n ( k k ( k + 1 ) / 2 ) 2 = k = 1 ∑ n ( 2 k + 1 ) 2
where the last two equalities follows by sum of first k positive integers formula.
Now, just shift the index. For the case of n = 1 6 , we have,
S 1 6 = k = 1 ∑ 1 6 ( 2 k + 1 ) 2 = 4 1 k = 2 ∑ 1 7 k 2 = 4 1 ( 6 1 ( 1 7 ) ( 1 7 + 1 ) ( 3 4 + 1 ) − 1 2 ) = 4 4 6
where the last two equalities follows by sum of squares formula.
You can also write down the general result for S n which is,
S n = 4 1 ( 6 ( n + 1 ) ( n + 2 ) ( 2 n + 3 ) − 1 ) ∀ n ∈ Z +
This general result is obtained by proceeding similarly as done for the n = 1 6 case and is left as an exercise to the interested reader.
I really like the comment in the Challenge Master note regarding the use of Nicomachus' Theorem. The series can also be represented as,
S n = k = 1 ∑ n k 2 T k 2
where T k is the k th triangular number . Applying Nichomachus' Theorem, we get,
S n = k = 1 ∑ n k 2 ∑ i = 1 k i 3 = k = 1 ∑ n ( 2 k + 1 ) 2
where the last equality follows by sum of cubes formula and simple algebraic manipulation.
The rest is the same as the conclusion of the original solution.